Sistema de Gestión de Sub-Contratos - Hernández-Soto, Adrián (Instituto Tecnológico de Costa Rica, 2018)
Bilco Costa Rica is a building company focused on customer service, it stands out as a non-traditional construction company with a large number of high-end projects completed despite its short history in the country. In this company various processes are carried on paper or tools are used that does not solve all the processes that the company performs. For this reason, the information technology (IT) department is working on a system where most of the processes of the company can be performed from a single software system to carry out a better order of the information that is generated. For the Professional Practice will be performing the Sub Contracts system, which will be contributing with the subcontracts that the company makes when it comes the time to start new projects or remodeling projects. With the system described above it is intended that handmade, Excel and Word documents will be replaced. This project has as a priority to independence the software company ERP Softland that has been used, because it has not as complied with the requirements of the company to carry out the subcontracting process.
Informe Final de Graduación (Bachiller en Ingeniería en Computación). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Computación, 2018.
Keywords: Gestión de proyectos; Automatización; Construcción; Software; Servicio al cliente; Proveedores; Empresas; Datos